At first sight - Sparks, Nicholas (New York : Grand Central Pub., 2007)
Finding himself happily married, living far from his New York City origins, and anticipating the birth of his first child, Jeremy Marsh receives a mysterious message that reopens wounds from the past and changes the course of his marriage.
Keywords: American fiction; Married people -- Fiction; North Carolina -- Fiction